Uji Kausalitas : Utang Luar Negeri dan Capital Flight di Indonesia, 1974-2002 - Dini Yuniarti (Economic Journal of Emerging Markets, 2005)
Some economists have argued that there is no relationship between external debt and capital flight, while others have detected such a relation. Boyce and Ndikumana (2002) distinguish four possible causal links such as, debt-driven capital flight, debt fueled capital flight, flight-driven capital flight, and flight fueled external borrowing.The study examines a causal relationship between external debt and capital flight of Indonesia for the period 1974-2002. We use error correction model to examine a causal rela¬tionship. We find external debt related to capital flight on Indonesia as a feedback/bilateral causality. This empirical evidence supports the debt fueled capital flight and flight fueled external borrowing hypothesis.     Keywords: causal relationship, external debt, capital flight